Reduction of signal reflection along through silicon via channel in high-speed three-dimensional integration circuit - 刘晓贤 朱樟明 杨银堂 王凤娟 丁瑞雪 (Chinese physics B, 2014)
The through silicon via （TSV） technology has proven to be the critical enabler to realize a three-dimensional （3D） gigscale system with higher performance but shorter interconnect length. However, the received digital signal after trans- mission through a TSV channel, composed of redistribution layers （RDLs）, TSVs, and bumps, is degraded at a high data-rate due to the non-idealities of the channel. We propose the Chebyshev multisection transformers to reduce the signal reflec- tion of TSV channel when operating frequency goes up to 20 GHz, by which signal reflection coefficient （$11） and signal transmission coefficient （$21） are improved remarkably by 150% and 73.3%, respectively. Both the time delay and power dissipation are also reduced by 4% and 13.3%, respectively. The resistance-inductance-conductance-capacitance （RLGC） elements of the TSV channel are iterated from scattering （S）-parameters, and the proposed method of weakening the signal reflection is verified using high frequency simulator structure （HFSS） simulation software by Ansoft.